(untitled) (International Journal of Innovative Computing, 2017)
In the holy Quran, verses about same or similar topics are scattered in different chapters. Moreover, it is Â hard for users to remember many keywords of a verse while they search for nature related concepts of Quran. In such a situation, semantic search can be very useful. This paper starts with a refined ontological model to facilitate the search of nature related concepts mentioned in Quran. It shows the implementation of a Fuseki server based sparql endpoint to enable the semantic search. We also integrate Jena Application Programming Interface (API) with the ontology and develop a Java application to access and query the ontology. We demonstrate that, it is possible to apply Web Ontology Language (OWL) reasoning on Quranic data and that application of the reasoning brings out new implicit facts. Finally, we compare the specific query answering capacity of our nature related ontological model of Quran to a general ontological model of Quran. Thus, we show that an ontology designed for nature related concepts of Quran can better answer nature related queries.